2019
DOI: 10.18502/ijml.v6i4.1998
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Haemolytic Significance of Red Cell Antibodies among Dangerous Universal Donors in a Tertiary Care Hospital in South India

Abstract: Background and Aims: A subgroup of group O individuals called ‘dangerous universal donors’ have immune (IgG) anti A and anti B antibodies which are active at 37˚C and capable of reacting with the red cells and causing lysis. The aim of this study was to find the prevalence of dangerous O group among the voluntary donor population and to assess the relation between the degree of haemolysis and the antibody titre. Materials and Methods: Group O donors excepting those with history of transfusion or pregnancy were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…25 The high prevalence of haemolysin in this study is comparable to that (52.8%) reported by a study in Abakaliki, Nigeria, in 2014. 25 Lower haemolysin prevalence rates have been reported by studies among healthy blood donors in South India (10.8% in 2019), 26 Abidjan, Côte d’lvoire 18 (35.1% in 2016), Lagos, Nigeria 10 (30.3% in 2015), Bauchi, Nigeria 27 (22.2% in 2015), Anambra, Nigeria 28 (16.06% in 2015), Tunisia 14 (6.6% in 2008), Ilorin, Nigeria 11 (23.2% in 2001), and Nigeria 12 (30.6% in 1990). A higher prevalence of 69.0% was reported in a 2012 study on healthy blood donors in Bangkok, Thailand.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…25 The high prevalence of haemolysin in this study is comparable to that (52.8%) reported by a study in Abakaliki, Nigeria, in 2014. 25 Lower haemolysin prevalence rates have been reported by studies among healthy blood donors in South India (10.8% in 2019), 26 Abidjan, Côte d’lvoire 18 (35.1% in 2016), Lagos, Nigeria 10 (30.3% in 2015), Bauchi, Nigeria 27 (22.2% in 2015), Anambra, Nigeria 28 (16.06% in 2015), Tunisia 14 (6.6% in 2008), Ilorin, Nigeria 11 (23.2% in 2001), and Nigeria 12 (30.6% in 1990). A higher prevalence of 69.0% was reported in a 2012 study on healthy blood donors in Bangkok, Thailand.…”
Section: Discussionmentioning
confidence: 96%
“…A higher prevalence of 69.0% was reported in a 2012 study on healthy blood donors in Bangkok, Thailand. 29 These differences in prevalence rates may be due to the admixture of blood of immigrants as a result of intermarriages, 20 variations in serum-cell ratios, 30 or differences in geographical location, 26 particularly due to the differences in the degree of exposure to gastrointestinal parasites 22 and mosquitoes. 13 , 14 , 15 It has been reported that higher serum-cell ratios increase the tendency for red cell lysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Group A donors followed with a rate of 11.4%, while group B donors accounted for 5.9% of cases. This observation explains why most studies on haemolysins have focused mainly on group O donors [10][11][12][13][14][15][16][17][18]22]. The predominance of group O is explained by their high frequency in the world population and by the absence of A and B antigens on the surface of their red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly useful in emergency situations where blood grouping could delay medical treatment or where there is a shortage of isogroup blood [1][2][3][4][5]. It is important to note, however, that for group Of individuals with ABO haemolysins, their blood must be reserved for isogroup transfusions because of the risk of incompatibility [1], hence their occasional nickname of "dangerous universal donors" in such circumstances [22]. We also found differences in the prevalence of different haemolysin specificities according to blood group.…”
Section: Discussionmentioning
confidence: 99%